Is Red Blood Cell Distribution Width (RDW) a Negative Predictor of Repeated Implantation Failure? - Özlem Kayacık Günday; Oya Aldemir; Runa Özelçi; Serdar Dilbaz; Emre Başer; Özlem Moraloğlu Tekin (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: Repeated implantation failure (RIF) after in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) can be a devastating reality for some patients with infertility. Our objective was to evaluate the potential role of the complete blood count (CBC) parameters, on treatment outcome in patients with repeated IVF implantation failure. Methods: This retrospective clinical study, involving a total of 173 patients, consisted of 64 patients with RIF who underwent a fresh IVF-ET cycle, underwent 3 or more IVF cycles, and 109 patients in the control group who became pregnant in the first IVF-ET cycle. Results: Duration of infertility, number of grade 2 embryos and red cell distribution width (RDW) were significantly higher in RIF patients (p < 0.001, p < 0.001, p = 0.02). The number of 2 pronucleus (PN) showed a significant positive correlation with the fertilization rate (FR) (r: 0.6; p < 0.001). To understand the effects of CBC parameters on FR, the model established with the number of RDW, number of grade 2 embryos and the number of 2 PN proved to be significant (ANOVA, p < 0.001). Conclusions: RIF patients have higher RDW, longer duration of infertility, and higher number of grade 2 embryos. Elevated RDW may negatively impact FR. The number of 2 PN increased FR.